Anti-breast cancer effect of eupatorin in vitro and in vivo - Abd Razak, Nursyamirah (2018)
Triple-negative breast cancers (TNBC) represent the most aggressive form of breast cancers and their treatments are challenging due to the tumour heterogeneity and chemo-resistance which have been the major obstacle. Chemotherapy using synthesized drugs is commonly used to treat breast cancer. However, this kind of treatment may cause negative side effects to the patients. Recently, eupatorin had been reported to be a potent candidate to inhibit breast cancer cells proliferation. Eupatorin is a product that belongs to a flavonoid family. However, the detailed information on the efficacy and mechanisms of eupatorin as an anti-breast cancer agent in vitro and in vivo is very limited. In this study, the cytotoxic effect, anti-proliferative action, cell cycle arrest and apoptosis induction of eupatorin on the human breast carcinoma cell lines of MDA-MB-231 (estrogen-receptor negative), MCF-7 (estrogen-receptor positive) and on a cell line derived from normal mammary tissue, MCF-10a were studied. In addition, the in vivo antitumour effect of eupatorin was tested on the Balb/c mice challenged with 4T1 murine mammary cancer cells. MTT assay showed that eupatorin and tamoxifen (positive control) had cytotoxicity effects against the cancerous cell lines of MCF-7, MDA-MB-231 and 4T1 cells. At 48 hours, eupatorin at 14.52 μΜ inhibited cell proliferation of MCF-7 and MDA-MB-231 by 50%. However, the IC50 of tamoxifen at 48 hours to inhibit MCF-7 and MDA-MB-231 cells proliferation was 5.23 μM and 7.22 μM, respectively. In contrast, the IC50 value of eupatorin at 48 hours for MCF-10a was significantly (p<0.05) high with 58.09 μM. Through scratch assay, eupatorin (14.52 μM) prohibited the complete closure of scratched area in MDA-MB-231 cells after 24 hours incubation. In addition, Boyden chamber assay revealed that eupatorin at 14.52 μM inhibited the aggressiveness of MDA-MB-231 cells where less than 40% of the cells were migrating and invading the membrane in the Boyden chamber. Moreover, ex vivo model using aortic ring from Balb/c mouse suggested that eupatorin can act as anti-angiogeneic due to the inhibition of aortic sprouting activation in mouse aortic rings assay. In cell cycle analysis using MCF-7 and MDA-MB-231 cells, eupatorin enhanced the accumulation of cells in sub Gθ/G1. At 48 hours, the number of MCF-7 and MDA-MB-231 cells accumulated in sub Gθ/G1 was 27.52 ± 2.06% and 42.75 ± 4.67% respectively. Concurrently, the percentage of early apoptotic of respective MCF-7 and MDA-MB-231 cells were 28.38 ± 0.24% and 64.04 ± 0.66%. In addition, the population of late apoptotic cells of MCF-7 and MDA-MB-231 were 40.26 ± 0.33% and 18.27 ± 0.57%, respectively. In contrast, more than 95% of the untreated cells for both cell types were distributed in Gθ/G1 phase at 48 hours. In gene expression assay, eupatorin up-regulated the pro-apoptotic genes such as Bak1, Bax, cytochrome c, SMAC/Diablo and HIF1A in both cell lines and concurrently down-regulated the anti-apoptotic genes such as VEGFA and Bcl2L11. Furthermore, Western Blot analysis revealed that eupatorin could inhibit cells proliferation in MDA-MB-231 and MCF-7 cells through depletion of Cdc2 and Chk1 protein level respectively followed by the activation of Chk2 protein which lead to the Akt and MAPK signalling pathway blockage. Moreover, caspases activation confirmed that eupatorin initiated apoptosis via intrinsic pathway in MCF-7 and MDA-MB-231 cells due to high fold change number of activated caspase 9 compared to caspase 8. In vivo study showed that eupatorin at the dosage of 20 mg/kg was sufficient to delay the tumour development. Histologic assessment revealed that eupatorin (20 mg/kg) has significantly (p<0.05) enhanced the number of apoptotic cells in tumour. Additionally, clonogenic assay showed that eupatorin (20 mg/kg) has potently reduced the number of invaded 4T1 cells in lung where 30.70 x 103 ± 10.89 blue colonies were detected whereas the untreated lung possessed 400.00 x 103 ± 28.28 blue colonies. Besides, eupatorin (20 mg/kg) also has significantly (p<0.05) increased the NK cells and T-cell responses to 4T1 tumour cells in splenocytes assay. In immunophenotyping assessment, eupatorin (20 mg/kg) enhanced the stimulation of NK1.1+CD3 and CD8+ expression by 4.75 ±0.37% and 8.83 ±0.36% respectively when compared to the untreated (NK1.1+CD3 :3.57% ± 0.13; CD8+ :4.30%±0.07). Cytokine assay revealed that IL-1β was significantly (p<0.05) suppressed to 812.00 ± 57.50 pg/mL while the IFN-γ was enhanced to 1407.41 ± 25.66 pg/mL compared to the untreated (IL-1β :1045.33 ± 257.98 pg/mL; IFN-γ :1185.19 ± 187.86 pg/mL). Western blot analysis showed that eupatorin (20 mg/kg) could delay the tumour progression, invasion and migration through MAPK pathway blocking. Additionally, gene expression assay revealed that eupatorin (20 mg/kg) inhibited the regulation of gene MMP9, TNFα, and IL-1β expression sufficiently.Taken together, eupatorin is a potent candidate as anti-breast cancer agent that has anti-proliferative and anti-metastasis activities on breast cancer cells which should be examined further in clinical study.